PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJARSISWA KELAS IV SD NEGERI 011 BANJAR XII - Sepni Yunita; Otang Kurniaman; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was aimed to increase students achievement of social lesson in IV grade year of 2015/2016. The subject of this research in students IV grade of state Elementary School 011 Banjar XII which is total of 18 students, consisted of 8 girls and 10 boys. This was a classroom research which has two cycles which was conducted on April 06th to May 13th 2015. The data shown that either learning process or students achievement increased. This was found from students and teachers scores in learning process increased. First cycle at the first meeting teacher’s activity was 66,6%categorized as good and increased 4,2% at the second meeting as 70,8% categorized as good. Meanwhile at the second cycle at the first meeting the percentage of teacher’s activity increased as 83,3% categorized as very good and in the second meeting it increased as 8,4% so the percentage became 91,7% categorized as very good. While students activities in learning process also increased. At the first cycle in the first meeting, the percentage of students activities was 62,5% categorized as good and the second meeting it increased as 4,1% so became 66,6% categorized as good. At the second cycle in the first meeting it increased to 83,3% categorized as very good. At the second meeting the percentage of students’ activities increased as 4,2% became 87,5% categorized as very good. However, students’ achievement also increased. The basic score of daily examination as 12,44% which 10 students passed and 8 students failed. The ending of daily examination was 55,56% and the average 67,78 on the passing grade. The second daily examination also increased from daily examination of as 16,39% which 15 students passed and 3 students failed. The ending of second daily examination was 83,33% and the average was 78,89. Based on the explanation above it can be concluded that the implementation cooperative learning make a match thype to increase students achievement in social lesson of students IV grade of State Elementary School 011 banjar XII.Key Words : Cooperative Learning Think Pair Share Thype, Social Lesso